Wizualność norwidowskiej metafory (na przykładzie "Fortepianu Szopena") - Niewczas, Łukasz (Colloquia Litteraria, 2012)
Norwid’s Visual Metaphor (using the example of ‘Chopin’s Grand Piano’) The article deals with the analysis of the visual metaphor present in Norwid’s writings. The author’s microanalyses point to a certain type of ‘semiotic image’ prevalent in Norwid’s literary output.